A Public Choice Approach to Motivation People in Bureaucratic Organizations - Spicer, Michael W. (Academy of Management Review, 1985)
This paper examines the problem of motivating people in organizations from a public choice viewpoint. A number of propositions are derived deductively from assumptions regarding individual goals, discretion, and preferences. These suggest how managers can improve productivity by changing either incentive systems or work group size, job design, and personnel rotation practices.